Modulation of intestinal and systemic immune responses to a fed protein antigen, in mice. Issue 7 (July 1986) - Strobel, S; Ferguson, A
Abstract : Feeding of a protein antigen to normal adult mice results in systemic immunologic hyporesponsiveness (oral tolerance). Local mucosal cell mediated immunity is not usually elicited. The objectives of these experiments were to abrogate the induction of oral tolerance and concomitantly to induce a local mucosal cell mediated immune response in mice; and thereby to establish which facets of intestinal physiology or immunology are relevant to the induction of normal, mainly suppressor immune responses to a fed antigen. Protein antigen (ovalbumin) was fed to animals in whom immune status had been modulated by intraperitoneal injection of N-acetyl-muramyl dipeptide (MDP), by induction of a graft versus host reaction, or naturally, by virtue of immaturity. The induction of oral tolerance was prevented in all treatment groups. In a second series of experiments mice were orally immunised as before, rested for four weeks, and then challenged with ovalbumin in their drinking water for 10 days. Jejunal architecture was not altered by the antigen challenge, but MDP treated and immature animals which had been sensitised to ovalbumin and later re-exposed to the same antigen had significantly higher intraepithelial lymphocyte counts than appropriate controls. Factors which may lead to abrogation of oral tolerance and induction of intestinal hypersensitivity are discussed in relation to food allergic diseases in man.